ANALISIS KEBIASAAN HUBUNGAN SEKSUAL KELOMPOK BERISIKO HIV (PADA LAKI-LAKI) TERHADAP HASIL TES HIV DI KLINIK IMS PUSKESMAS TELADAN TAHUN 2017 - christina aprilia sitorus; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACTTransmission of HIV through sexual contact with infected people is the most common way arround 80%-90% total cases in the world. Based on data Department of Health, risk factor of AIDS transmission in 2015, with highest proportion is heterosexual (82,8%), followed by homosexual (7,4%). This rese- arch is aimed to analysing habits of sexual intercourse on hiv risk group (on men) and want to know the proportion of using condom to HIV test result in sexually transmitted infections clinic of Teladan Health Centre in 2017. This research is analitic with cross-sectional design. Sample consist of 85 people chosen by purposive sampling. Data collected by interviewed based on qu- estionnaire filling. Data bivariat analysis using Chi-square test and fisher’s with confidence interval 95% (α=0,05). The result shows that the highest proportion of risk group based on characteristics respondents are, age ≤40 years (90,6%), last education SMA/SMK (44,7%), occupation entrepreneur (32,9%), unmerried (83,5%), risk group LSL (51,8%), sexual intercourse type III (anal, anal-oral, anal-vaginal, anal-vaginal-oral) (67,1%), using condom risky category (71,8%) and test HIV positive (60,0%). The statistical test give significant differences among HIV test result ba-  sed on sexual intercourse (p=0,001 and p=0,008), give no significant differences among HIV test result based on marital status, risk group and using condom. It’s suggested to the NGO/health centre, more targeted to the productive age group, the IMS/VCT staff more often to give counseling about risky sexual beha- viour especially anal sex, preferably the risk group more often do self checking to IMS/VCT services and intersectoral relationship between health centre, religion and education to suppress HIV/AIDS transmission.Keywords : HIV, Risk Group, Sexual Intercourse, Health Centre